Ureditev javno-zasebnega partnerstva v Sloveniji - Prodan, Irena (Podjetje in delo, 2015)
The increasing demands of the business and social environment are the driving force of development of each country. For a faster and more efficient implementation of the objectives of the society the state needs to provide a modern and powerful infrastructure. The increase in private sector activities and liaiseing with the public sector in the field of infrastructure has become a worlwide trend over the last decade. The positive effects of these links have been realized in practice by many EU Member States. Therefore, the European institutions also give strong support to the introduction of public-private partnerships in all members of the European Union. With the introduction of the European Directives the competitive market is expanding in this area, thus increasing the possibilities of the pan-European integration.
Keywords: European Union; Evropska unija; javno-zasebno partnerstvo; pravna ureditev; Slovenia; Slovenija